Training on Foot Care for Three Wheeled Motor Vehicles - Soleh, Abdullah Robeid; Rodzak, Muhammad Ferry; Zuhairi, Rafi; Farisi, A. Wahid Al; Hadiyyatullah, Muhammad Nabiil; Ridlo, Muhammad Zainur (Journal Of Humanities Community Empowerment, 2025)
Three-wheeled motor vehicles are widely used for small-scale transportation, especially in rural and urban areas. However, users often lack awareness of proper maintenance, particularly in undercarriage components like braking systems and tires, which are critical for safety. This training, held at the University of Muhammadiyah Jember, aimed to improve students’ understanding and skills in maintaining these components. The methods included theoretical instruction, hands-on practice, and post-training evaluation. Results showed increased participant comprehension and engagement, although initial knowledge levels varied. The activity demonstrated that basic technical education can significantly improve awareness and competence in vehicle maintenance. It is expected that participants can apply this knowledge in their daily lives and promote better maintenance practices within their communities